SAM of Gliotoxin on Gold: A Natural Product Platform for Sugar Recognition based on the Immobilization of Canavalia brasiliensis lectin (ConBr). (1st July 2017) - Abreu, Dieric S.; Sousa, Ticyano P.; Castro, Caio B.; Sousa, Mayara N.V.; Silva, Thiago T.; Almeida-Neto, Francisco W.Q.; Queiros, Marcos V.A.; Rodrigues, Bárbara S.F.; Oliveira, Maria C.F.; Paulo, Tércio F.; Cavada, Benildo S.; Nascimento, Kyria S.; et al.
Graphical abstract: Highlights: Gliotoxin: a diketopiperazine isolated from marine-derived fungus that modifies gold. ConBr lectin successfully interacts with gliotoxin. A novel gold surface coated with a gliotoxin-ConBr multilayer is reported. Sugar-recognition ability of ConBr remains active on surface as proved by SPR. Hydrogen bonds are the major contributions connecting the sugar molecules to the metallic sites of ConBr. Abstract: We report the successful fabrication of a novel gold surface coated with a thiol-lectin multilayer that showed specific interaction towards D-mannose sugars. Firstly, the gold surface was spontaneously modified with gliotoxin (gtx), a sulfur containing diketopiperazine isolated from marine-derived fungus, and fully characterized by electrochemical, EIS, SPR and SERS techniques. The results indicated the sulfur bridge of gtx is broken upon adsorption and the molecules are flat lying on gold with surface coverage of 2.3 × 10 −10 mol cm −2 and reductive desorption potential of −0.87 V vs Ag/AgCl, i.e. strongly chemisorbed on gold. The real-time monitoring of the immobilization of Concanavalin Br (ConBr) lectin (6.9 × 10 −12 mol cm −2 ) on the gold surface modified with gliotoxin (Au/gtx) was performed by SPR which was also used to prove the recognition capability of ConBr towards D-mannose remains active on Au/gtx. Comparative studies using 11-mercaptoundecanoic acid and cysteine on gold show the interaction between the thiol layer with ConBr involves a network of hydrogen bonds and that the SAM formed with gliotoxin is the most robust monolayer. Impedimetric measurements in solution containing [Fe(CN)6 ] 3−/4− redox probe and D-mannose sugar at different concentrations indicate hydrogen bonds are the major intermolecular contributions connecting the sugar molecules to the sugar recognition sites of ConBr where Ca 2+ and Mn 2+ ions are inserted..